Recommendations for Diagnosis and Treatment of Pseudohypoparathyroidism and Related Disorders: An Updated Practical Tool for Physicians and Patients - DEMİRCİOĞLU, SERAP (KARGER, 2020)
Patients affected by pseudohypoparathyroidism (PHP) or related disorders are characterized by physical findings that may include brachydactyly, a short stature, a stocky build, early-onset obesity, ectopic ossifications, and neurodevelopmental deficits, as well as hormonal resistance most prominently to parathyroid hormone (PTH). In addition to these alterations, patients may develop other hormonal resistances, leading to overt or subclinical hypothyroidism, hypogonadism and growth hormone (GH) deficiency, impaired growth without measurable evidence for hormonal abnormalities, type 2 diabetes, and skeletal issues with potentially severe limitation of mobility. PHP and related disorders are primarily clinical diagnoses. Given the variability of the clinical, radiological, and biochemical presentation, establishment of the molecular diagnosis is of critical importance for patients. It facilitates management, including prevention of complications, screening and treatment of endocrine deficits, supportive measures, and appropriate genetic counselling. Based on the first international consensus statement for these disorders, this article provides an updated and ready-to-use tool to help physicians and patients outlining relevant interventions and their timing. A life-long coordinated and multidisciplinary approach is recommended, starting as far as possible in early infancy and continuing throughout adulthood with an appropriate and timely transition from pediatric to adult care.
Keywords: Acrodysostosis; Bone disorders; Brachydactyly; Calcium and phosphate metabolism; Consensus; Diagnosis; Management; Ossification; Parathyroid hormone; Pseudohypoparathyroidism; Treatment; ALBRIGHT HEREDITARY OSTEODYSTROPHY; PROGRESSIVE OSSEOUS HETEROPLASIA; IDENTIFIES PDE4D MUTATIONS; HORMONE-RELEASING-HORMONE; STIMULATORY G-PROTEIN; PSEUDO-PSEUDOHYPOPARATHYROIDISM; SKELETAL RESPONSIVENESS; INCREASED PREVALENCE; PARATHYROID-HORMONE; ENERGY-EXPENDITURE